Post-COVID condation - saad, Rema (My University, 2022)
introduction: Post COVID was also found to grow with age, and was more likely to afflict women, according to a study by Imperial College London. Long COVID was found to be more common among those who smoke, live in low income areas, or had severe COVID sickness that required hospitalization.